Assessment Of Antibiotic Production Potential In Two Actinomycetes Against Vancomycin Resistant Enterococci - M. KALPANA DEVI,; R.USHA, (International Journal of Pharma and Bio Sciences, 2015)
Crude extracts of two actinomycetes ACT24 and ACT25 were analysed for antibacterial activities against wide range of bacterial strains. The extracts showed antibacterial activities against both Gram-negative and Gram-positive test bacteria with zone of inhibition ranging between 2 and 15mm. The minimum inhibitory concentration of the extracts against the test bacteria ranged from 1.2mg/ml – 4.2 mg/ml. The extracts of ACT24 and ACT25 exhibited concentration time dependent killing of Vancomycin resistant enterococcus with a 4.62Log10 and 3.46Log10 reduction in viable counts respectively. ACT24 ethylacetate extract exhibited prolonged post antibiotic effect against vancomycin enterococci giving a significantly more favorable effect than reference compound which is most commonly used systemic antibiotic chloramphenicol. This assessment reveals that antibiotic from ACT24 has potential to inhibit the vancomycin resistant enterococci and this can be exploited for further treatment in future by analysing the structure of the compound.